Detection of Tetracycline residues in broiler meat samples in Damascus Countryside Governorate- Syria (Journal of Hama University, 2022)
A total of 24 chicken muscles samples was collected from four cities in Damascus Countryside Governorate (Duma, Maraba, Nabk and Dmer). The samples analyzed for tetracycline residues (oxytetracycline, doxycycline and chlortetracycline). The tetracycline residues were determined by using HPLC technique (according to AOAC method No 995.09, 1995), with following conditions: C`18 column, mobile phase containing: acetonitrile: methanol: oxalic acid (30:10:60), 350 nm wave length, 1 ml\min flow rate. Results showed that 12 samples (from 24 samples) were positive for oxytetracycline and doxycycline residues and three samples are positive for chlortetracycline residues only. doxycycline residues in 5 samples and oxytetracycline residues in tow samples were higher than local MRL (100 µg/kg w.w), but chlortetracycline residues were lower than MRL. The changes in the tetracycline concentrations in the muscles samples is not significant differences (P>0.05) for all studded samples. The result showed extensive use of tetracycline compounds and These high levels of antibiotic residues may be attributed to the unpaid attention to the withdrawal period of the antibiotics.